2002
DOI: 10.1007/s00264-002-0355-3
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a lateral flare feature on implant stability

Abstract: We reviewed the X-rays of 109 patients with 115 primary total hip replacements utilizing a lateral flare cementless stem to assess axial migration and stability. The average follow-up was 48.6 (24-104) months. The average subsidence at 2 years was 0.32 mm, remaining at a level below 1 mm for the duration of the followup. Even though there were ten reoperations involving either the change of a polyethylene liner and the acetabular component, or both, none of the patients required a femoral stem revision. It was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
38
0
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 12 publications
1
38
0
5
Order By: Relevance
“…Even though the use of a collar may increase the axial compression to the bone [5], it may impede the wedging effect of the lateral flare [18]. Its value as an additional feature to maximize prosthesis-bone contact in the primary setting is secondary to the stabilizing effect imposed by the extended proximal geometry of the implant [17] and the collar, therefore, is not a feature of the design of this stem.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Even though the use of a collar may increase the axial compression to the bone [5], it may impede the wedging effect of the lateral flare [18]. Its value as an additional feature to maximize prosthesis-bone contact in the primary setting is secondary to the stabilizing effect imposed by the extended proximal geometry of the implant [17] and the collar, therefore, is not a feature of the design of this stem.…”
Section: Discussionmentioning
confidence: 99%
“…The sturdy fixation achieved by engaging the metaphysis and loading the femur both medially and laterally creates an inherently stable construction [17,24,25]. The proximal anterior bow and the flat posterior surface create a trapezoidal proximal cross-section allowing for a near complete filling of the metaphysis in both the anterior-posterior and the mediallateral planes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fatto et al [9] further refined this model in 1995 and showed that the lateral femoral cortex can be effectively used to carry compressive loads. Leari et al [10] reviewed radiographs of primary THR with a lateral flare for axial migration and stability. They concluded that a prominent lateral flare provided significant initial stability through early bony ingrowth, which is vital for long term implant stability and provision against stress shielding.…”
Section: Discussionmentioning
confidence: 99%